Organic-inorganic layered membrane for selective hydrogen permeation together with dehydration - Miyajima, K.; Eda, T.; Nair, Balagopal; Iwamoto, Y. (Elsevier BV, 2012)
Gas and vapor permeations of microporous amorphous silica membranes derived from commercial perhydropolysilazanes (PHPS) were investigated. Amorphous silica membranes were synthesized by a conventional heat treatment at 650°C in air, and by a novel method using irradiation of air plasma. In the synthetic study of amorphous silica membranes by the conventional heat treatment, the membrane was formed on a porous silicon nitride tubular support. Two types of PHPS, with and without methyl (-CH 3) groups at the ends of the silicon-nitrogen backbone were used, and the amorphous silica membrane derived from the PHPS having -CH 3 end groups was found to exhibit higher hydrogen permeance and hydrogen/nitrogen perm-selectivity compared to those of the membrane derived from the end group-free PHPS. Then, by using a novel air plasma irradiation technique, low temperature conversion of PHPS into amorphous silica was investigated. The results of Fourier-transform infra-red spectroscopic analysis showed that the PHPS having -CH 3 end groups was fully oxidized to yield amorphous silica after the irradiation for 60min. By this novel technique, an amorphous silica membrane was successfully formed on a polytetrafluoroethylene (PTFE) film attached on a porous alumina substrate. The layered membrane exhibited simultaneous functions of hydrogen separation together with dehydration as designed. By comparing the activation energies measured for the hydrogen permeation through the membranes synthesized in this study, it was estimated that the amorphous silica membranes synthesized by using the plasma irradiation were composed of the microporous random silicate network similar to those of the conventionally synthesized membranes. © 2012 Elsevier B.V.